Kapital(i) in zdravje - Kamin, Tanja (Teorija in praksa, 2011)
Rising life expectancy on one hand and increasing health inequalities on the other are an indicator of unequally distributed health improvements among people. The majority of social inequalities in health research are examined by a few socioeconomic factors. These are often distanced from the conceptual nature of class inequality. We argue that differences in health and health-related practices should be ascribed to conservation, as well as to the deepening of class inequalities. In this paper we assess how the structural system of social positions influences various interrelated resources that people can utilise and manipulate in the field of health. We conceptualise the relationship between socioeconomic factors and health practices and outcomes through Bourdieu's forms of capital: economic, social and cultural. We demonstrate that the forms of capital are highly interrelated and make a claim against reductionist approaches which in relation to health only examine one form of capital in isolation from the other forms of capital. People possess different forms of capital which constantly interact and only as such do they affect health status, health concerns and practices in the field of health.
Keywords: Družbena neenakost; Social inequality; Health; Zdravje; Socialni kapital (Sociologija); Social capital (Sociology); socialni kapital